1974
DOI: 10.1021/ja00822a014
|View full text |Cite
|
Sign up to set email alerts
|

p-Xylene clathrate of tris(1,8-naphthalenedioxy)cyclotriphosphazene. X-ray crystal and molecular structure

Abstract: Tris(l,8-naphthalenedioxy)cyclotriphosphazene (III) forms a clathrate inclusion adduct with p-xylene.An X-ray single-crystal study has shown that the p-xylene molecules are physically trapped in a fixed position within channels that penetrate the lattice. The naphthalenedioxy side groups of the host molecules (III) are bent at the oxygen atoms in such a way that strong host-host interactions stabilize the channel structure. The unit cell is triclinic, with space group P\ and with a = 8.206

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

1974
1974
2009
2009

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 6 publications
1
18
0
Order By: Relevance
“…The magnetic susceptibility of Cu(dpa)(TCNQ)2 increases with dedreasing temperature, but it does not obey the Curie-Weiss law. Figure 3, in which the magnetic susceptibility is plotted against reciprocal temperature, shows that the susceptibility can be reproduced well with the equation = a + y/T (6) This type of temperature dependence has been observed for some conducting TCNQ salts of copper chelates:2,20 a is ascribed to the temperature-independent paramagnetism of delocalized conduction electrons, and y/T is attributed mainly to localized unpaired electrons. The a and y values evaluated for Cu(dpa)-(TCNQ)2 are shown in Table II.…”
Section: Resultssupporting
confidence: 65%
“…The magnetic susceptibility of Cu(dpa)(TCNQ)2 increases with dedreasing temperature, but it does not obey the Curie-Weiss law. Figure 3, in which the magnetic susceptibility is plotted against reciprocal temperature, shows that the susceptibility can be reproduced well with the equation = a + y/T (6) This type of temperature dependence has been observed for some conducting TCNQ salts of copper chelates:2,20 a is ascribed to the temperature-independent paramagnetism of delocalized conduction electrons, and y/T is attributed mainly to localized unpaired electrons. The a and y values evaluated for Cu(dpa)-(TCNQ)2 are shown in Table II.…”
Section: Resultssupporting
confidence: 65%
“…Recent work has shown that the crystal structures of the inclusion adducts formed from 2 are greatly dependent on the structure of the guest . To date, structures 3 and 4 are known to form inclusion adducts with only a few small molecules. ,
1
…”
Section: Introductionmentioning
confidence: 99%
“…Spirocyclic systems with larger exo-rings include the tris(1,8-naphthalenedioxy) and the tris(2,2u-dioxy-1,1u-biphenyl) compounds 5 and 6, respectively [24]. Although 5 forms a clathrate with p-xylene, the nonplanar conformation of six-membered PO 2 C 3 rings does not support the D 3h symmetrical paddlewheel arrangement of 1 [25]. The 2,2u-dioxybiphenyl derivative 6 does not form inclusion compounds.…”
Section: Clathratesmentioning
confidence: 99%